Comparison of thrombocyte counts during the post-oral administration of aspirin and the Holothuria scabra ethanol extract in Wistar rats (Rattus norvegicus) - Dian Mulawarmanti; Rima Parwati Sari (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Long bleeding time is a risk factor in dental treatment, especially in patients who consume aspirin or other antithrombotic drugs. Holothuria scabra (H. scabra) are mostly echinodermata and have been studied in Indonesia; they contain omega-3 and glycosaminoglycans, with an influence of an antithrombotic drug. Purpose: This study aimed to investigate the thrombocyte counts during the post-administration of aspirin and the H. scabra extract in Wistar rats (Rattus norvegicus). Methods: This study was true experimental with a post-test control group design. The sample consisting of 30 healthy male Wistar rats (R. norvegicus) with a bodyweight of 150–250 g was divided into three groups (n = 10). The rats in Group 1 were given sodium carboxymethyl cellulose (Na CMC). The rats in Group 2 were given aspirin, and the rats in Group 3 were given the H. scabra ethanol extract with a 25 mg/200 g dose as per their body weight (BW). Oral administration was given for seven days. The rats’ blood was taken on the eighth day. The amount of thrombocyte was measured using Wright’s stain methods. The analysis of variance (ANOVA) and the Least Significant Difference (LSD) tests were conducted for data analysis (p < 0.05). Results: The thrombocyte counts (179.00 ± 10.56) in aspirin administration were lower than those in H. scabra (265.00 ± 18.54) and control groups (334.17 ± 13.9), with a significant difference between the groups (p = 0.0001; p < 0.05). Conclusion: This study indicates that the oral administration of aspirin and H. scabra decreases thrombocyte counts, whereas the administration of aspirin reduces thrombocyte counts to levels lower than those in H. scabra in Wistar rats (R. norvegicus).